SWITHING INTENTION DENGAN MEDIASI KETIDAKPUASAN NASABAH - Nurdin, Irvan Ryandi (Master of Management Diponegoro University, 2015)
In order to win and maintain customers in competitive situations today, service quality have important role in the bank service development. To maintain customer is bacome very important for a bank. The key to success in the bank competitive market is not depend on the interest (price), but in the service to create loyal customers. Building a loyal customer is the main weapon that a bank must have. Bank should not stop to create If they already give satisfaction to the ct/sfomer, but they should keep their efforts to make customers loyal and not switch in to other bank. Have loyal customers is the key of success for a bank to increase the market share and finally increase the interest. One of the efforts that done by PT. Bank Negara Indonesia (Persero) Tbk was applied the Total Quality Service /TQS) pn:â€ºgram which imp/emenfed in all kind of service of PT. Bank Negara Indonesia (Persero) Tbk.The samples of this study the saving customers of PT Bank Negara Indonesia (Persero) Tbk UKC Rembang, there are 150 respondent. The aim of this study is to test the low implementation of service quality, and the low of perceived quality toward customer dissatisfaction in order to decrease switching intention. To analyze the data, we use eâ€tmcturaI Equation Modeling (SEM) run by AMOS 16 software.The result shows that the low implementation of service quality variable have a po.sitive effect toward customer dissatisfaction, the low of perceived quality has a positive effect toward customer dissatisfaction, the low implementation of service quality variable have a positive effect toward switching intention, the low of perceived quality has a positive effect toward switching intention and customer dissatisfaction has a positive reflect toward switching intention.Â